Urgensi Pengaturan Nasional Atas Kegiatan Militer Asing Di Ruang Udara Indonesia Berdasarkan Hukum Internasional - Sri Wulan Dewi; Retno Ayu Radita; Raisa Aulia Adhani; Dewi Rahmawati Gustini (Jurnal Ilmiah Wahana Pendidikan, 2023)
Airspace is one component of a country's territory. Airspace consists of airspace above the land and territorial waters of a country. International recognition of airspace as part of state sovereignty provides strong legitimacy for Indonesia as a vast country. This condition can change if Indonesia is unable to control the aerospace area. the problem of violations of sovereignty boundaries that are often carried out by foreign military aircraft that can interfere with Indonesia's airspace. A country's airspace is usually regulated by the government through the country's civil aviation agency or aviation authority. They establish rules and procedures relating to airspace use, air navigation, civil aviation and air security. This research is conducted by identifying how the concept of state urgency over airspace through state control rights according to international law and national legislation. The research method used is normative legal research involving analysis of applicable legal regulations, collection and analysis of legal documents, and analysis of legal concepts underlying a problem. The results of the study concluded that both international law and national legislation have confirmed that every state has full sovereignty or state control rights over airspace over its territory, including the airspace above it.